Futures beyond dystopia : creating social foresight - Slaughter, Richard (Futures and education series., 2004)
How can dystopian futures help provide the motivation to change the ways we operate day to day?Futures Beyond Dystopia takes the view that the dominant trends in the world suggest a long-term decline into unliveable Dystopian futures. The human prospect is therefore very challenging, yet the perception of dangers and dysfunctions is the first step towards dealing with them. The motivation to avoid future dangers is matched by the human need to create plans and move forward. These twin motivations can be very powerful and help to stimulate the fields of Futures Studies and Applied Foresight. Thi.